2017
DOI: 10.5032/jae.2017.02143
|View full text |Cite
|
Sign up to set email alerts
|

Supervised Agricultural Experience Instruction in Agricultural Teacher Education Programs: A National Descriptive Study

Abstract: Faculty in agricultural teacher education programs are responsible for preparing future teachers to lead effective school-based agricultural education programs. However, agriculture teachers are having difficulty implementing supervised agricultural experience (SAE), even though they value it conceptually as a program component. In an effort to improve SAE instruction in teacher education, the American Association for Agricultural Education has adopted a guiding philosophy and competencies for teacher preparat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
1
1
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 12 publications
1
3
0
Order By: Relevance
“…As part of the student teaching experience, preservice agriculture teachers were frequently required to assist SBAE students with recordkeeping as well as in completing award and degree applications. The prevalence of record book simulations and experiences in student teaching support the findings reported by Rank and Retallick (2016) regarding the perception of agricultural teacher educators that recordkeeping was being taught at an applied level in agricultural teacher education programs. Although recordkeeping was often taught as a concrete experience, no evidence was identified within the documents that indicated the transformation of the experience through reflective observation or active experimentation.…”
Section: Summary Of Findingssupporting
confidence: 77%
See 2 more Smart Citations
“…As part of the student teaching experience, preservice agriculture teachers were frequently required to assist SBAE students with recordkeeping as well as in completing award and degree applications. The prevalence of record book simulations and experiences in student teaching support the findings reported by Rank and Retallick (2016) regarding the perception of agricultural teacher educators that recordkeeping was being taught at an applied level in agricultural teacher education programs. Although recordkeeping was often taught as a concrete experience, no evidence was identified within the documents that indicated the transformation of the experience through reflective observation or active experimentation.…”
Section: Summary Of Findingssupporting
confidence: 77%
“…SAE is included at varying points throughout the agricultural teacher education curriculum (Rank & Retallick, 2016;. The need exists to identify the SAE content and its placement within agricultural teacher education course materials to provide evidence about how and where SAE instruction is included within agricultural teacher education.…”
Section: Conceptual Frameworkmentioning
confidence: 99%
See 1 more Smart Citation
“…Wolf went on to recommend professional development for SAE management and an increased concentration on the SAE domain for pre-service teachers. Rank and Retallick (2017) found that participants indicated teacher education programs train their students on how to categorize SAEs, but teachers were still not implementing them. Determining if changes in current SAE definitions and categories are providing clarity on the subject may help determine if current attempts to improve the implementation of project-based learning are effective.…”
Section: Conceptual Frameworkmentioning
confidence: 99%